"Photon recycling" can enhance cutaneous response to lasers: A pilot human study. Issue 1 (23rd December 2021) - Ross, Edward V.; Raythen, Jill; Anderson, R. Rox
Abstract: Background: Depending on wavelength and pigmentation, human skin can reflect up to 70% of incident laser light. Aims: We tested the hypothesis that returning ("recycling") this diffusely reflected light to the site of laser exposure would increase cutaneous response. Materials and Methods: Thirteen adult volunteers with Fitzpatrick skin types I–IV participated in this IRB‐approved study. Matched contralateral test sites on the volar forearms were exposed to a pulsed dye laser operated at 585 nm, 450 microseconds pulse duration in a uniform 5 mm circular exposure spot without skin cooling. On one arm, the laser handpiece was fitted with an aluminized hemispherical mirror with a reflectance of 67%. The minimum fluence causing skin purpura, and the purpura lesion diameter were measured. Results: The mean purpura threshold fluence with the reflector was 3.1 J/cm 2 (0.5 SD), and 3.7 J/cm 2 without the reflector (0.36 SD) ( p  < 0.001). The mean laser‐induced purpura lesion diameter was approximately 5.3 mm with the reflector and 5.0 mm without the reflector. Conclusion: Consistent with a theoretical model and in vitro measurements, this human study confirms that "recycling" reflected laser light can increase skin response. Potentially, the therapeutic response can also be improved with "photon recycling."